Implementasi ASCO (Analyzing, Solving Problems, ans Comparing) terhadap Pembelajaran Membaca Kritis - Nuria Reny Hariyati (Universitas Alma Ata, 2019)
AbstractResearch on overcoming exposure to radical issues with critical thinking on critical reading learning is still rarely done. This research is important to be carried out in the reading of the story to avoid radical issues that have been entered in university by using the Asco method (Analyzing, Solving Problems, Comparing). This research approach uses the Quasi-Times Design Series with Control Group experiment. The research data collection, namely the initial test scores and final tests. The experimental group was B2-18 and the control group was B3-18. Data analysis of this study used the One Way Anova SPSS test for Windows with a significance level of <0.05. The results of this study, namely (1) A homogeneous group test of 0.049 which was declared valid because> 0.05 to test this relationship; (2) Anova test of the two groups of 0,000 was declared significant because <0.05. The results showed that there was a significant influence of Asco (Analyzing, Solving Problems, Comparing) on critical reading learning. Keywords: Asco (Analyzing, Solving Problems, Comparing), Implementation, Critical ReadingLearning